2008
DOI: 10.1002/met.96
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of sea surface temperature and maximum potential intensity of tropical cyclones over the Bay of Bengal between 1981 and 2000

Abstract: From the consideration of thermal energy, the maximum intensity of tropical cyclones largely depends upon the Sea Surface Temperature (SST). In this paper an empirical relationship between SST and Maximum Potential Intensity (MPI) of tropical cyclones over the Bay of Bengal has been developed using a sample of 60 cyclones from 20 years data (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000). The relationship between SST and MPI is found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
0
18
1
Order By: Relevance
“…For instance, in case of Orissa Super Cyclone of October 1999, the peak intensity (140 knots) was 98% of MPI; in the case of the severe cyclonic storm Sidr of November 2007, peak intensity (115 knots) was 79% of MPI. The study (Kotal et al 2009b) showed that SST alone is not a dominant factor for the intensification of a tropical cyclone, but other factors, such as duration of cyclones over the sea and vertical wind shear, also play an important role in controlling the intensity. For the storms over the Indian Sea, the average observed peak intensity of cyclones reach up to 51% of their MPI (Kotal et al 2009b).…”
Section: Estimation Of Maximum Potential Intensity (Mpi)mentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, in case of Orissa Super Cyclone of October 1999, the peak intensity (140 knots) was 98% of MPI; in the case of the severe cyclonic storm Sidr of November 2007, peak intensity (115 knots) was 79% of MPI. The study (Kotal et al 2009b) showed that SST alone is not a dominant factor for the intensification of a tropical cyclone, but other factors, such as duration of cyclones over the sea and vertical wind shear, also play an important role in controlling the intensity. For the storms over the Indian Sea, the average observed peak intensity of cyclones reach up to 51% of their MPI (Kotal et al 2009b).…”
Section: Estimation Of Maximum Potential Intensity (Mpi)mentioning
confidence: 98%
“…The MPI provides useful information to a forecaster about the possible extreme intensity of tropical cyclones. For the Indian Seas, MPI is derived (Kotal et al 2009b) as:…”
Section: Estimation Of Maximum Potential Intensity (Mpi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Every year, low-pressure systems form in the Bay of Bengal during October-January and move towards the land to strike the coast. The occurrence of cyclones in northern Bay of Bengal has increased by *26 % during the last 120 years (Kotal et al 2009). …”
Section: Coastal Processesmentioning
confidence: 99%
“…The same linear form was later extended for TCs in the Indian Ocean basin by Kotal et al . (), which provides a reasonable estimation of V max in this ocean basin.…”
Section: Introductionmentioning
confidence: 97%